2009
DOI: 10.1111/j.1365-2893.2008.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

On‐treatment monitoring of adefovir therapy in chronic hepatitis B: virologic response can be assessed at 24 weeks

Abstract: Patients with chronic hepatitis B (CHB) who will and those who will not respond to adefovir (ADV) monotherapy need to be identified at an early stage in order to adjust treatment and prevent future development of antiviral resistance. In a single-centre cohort study, we investigated 76 CHB patients [50% hepatitis B e antigen (HBeAg)-positive] treated with long-term ADV monotherapy. During a median follow-up of 122 (24-185) weeks, 42 (55%) patients achieved virologic response (VR), defined as HBV-DNA levels <10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
3
19
3
Order By: Relevance
“…In addition, Pritchett et al [15] reported that lamivudine-resistant patients who had a more than 50% reduction in serum HBV DNA levels at week 24 of adefovir treatment were more likely to have undetectable serum HBV DNA levels at 1 year. In a single-center cohort study involving 76 patients with CHB treated with long-term adefovir monotherapy, serum HBV DNA levels at week 24 demonstrated a higher predictive value for virologic response at week 122 than serum HBV DNA levels at week 48 [10]. Of note, patients without undetectable serum HBV DNA levels at week 24 demonstrated a trend toward the emergence of adefovir resistance (P = 0.07).…”
Section: Adefovir Dipivoxilmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, Pritchett et al [15] reported that lamivudine-resistant patients who had a more than 50% reduction in serum HBV DNA levels at week 24 of adefovir treatment were more likely to have undetectable serum HBV DNA levels at 1 year. In a single-center cohort study involving 76 patients with CHB treated with long-term adefovir monotherapy, serum HBV DNA levels at week 24 demonstrated a higher predictive value for virologic response at week 122 than serum HBV DNA levels at week 48 [10]. Of note, patients without undetectable serum HBV DNA levels at week 24 demonstrated a trend toward the emergence of adefovir resistance (P = 0.07).…”
Section: Adefovir Dipivoxilmentioning
confidence: 95%
“…More recently, several studies have shown that serum HBV DNA levels at 24 weeks of adefovir are predictive of favorable outcomes in patients with CHB receiving adefovir [10,15,40]. In an adefovir-controlled, randomized, open-label trial of telbivudine involving 135 treatment-naive, HBeAg-positive adults with CHB, undetectable serum HBV DNA levels at week 24 were associated with high rates of virologic response at week 52 [40].…”
Section: Adefovir Dipivoxilmentioning
confidence: 99%
See 3 more Smart Citations